Livestock and poultry manure low temperature fermenting inoculant and application method thereof - LOU YUJIE; GAO YUNHANG; XU BO; GUO WEI; ZHOU HAIZHU; GOU CHANGLONG (2018)
The invention discloses a livestock and poultry manure low temperature fermenting inoculant, which comprises low temperature fermenting bacteria and functional emulsion according to a weight ratio of90-100: 10-15. Before fermentation, the manure is processed by lime powder to relieve the hardening of manure, the fermentation efficiency is improved, and at the same time, the lime powder can mask the stinky smell and maintains the compost environment. 本发明公开了种畜禽粪便低温发酵菌剂，它包括低温发酵菌与功能乳液，所述的低温发酵菌与功能乳液的重量比为90-100：10-15，本发明在发酵之前采用石灰粉处理，能够有效的改善粪便中的板结情况，提高发酵效率，同时，石灰粉可以气味可以进步掩盖恶臭，维持堆肥环境。